1974
DOI: 10.1111/j.1471-0528.1974.tb00460.x
|View full text |Cite
|
Sign up to set email alerts
|

The Outcome of Pregnancy After Failure of an Intrauterine Contraceptive Device

Abstract: Summary The outcome of 82 pregnancies associated with failure of an intrauterine device is reported. Four of the pregnancies were extrauterine, and 31 per cent of the 78 intrauterine pregnancies were legally terminated. Spontaneous or missed abortion occurred in 57 per cent of the remainder and over half of these abortions were in the second trimester. Threatened abortion, antepartum haemorrhage and manual removal of an adherent placenta were encountered more frequently than expected. One neonatal death due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1975
1975
2005
2005

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Vessey et a/. (1974) found that 8.9 per cent of all pregnancies with the IUCD in situ were ectopic, and Steven and Fraser (1974) found four ectopic pregnancies in a retrospective analysis of 82 pregnancies occurring after failure of an IUCD. The pregnancy rate with the device in situ is around 2 per 100 women per year (Vessey, personal communication).…”
Section: Intrauterine Contraceptive Devicesmentioning
confidence: 76%
“…Vessey et a/. (1974) found that 8.9 per cent of all pregnancies with the IUCD in situ were ectopic, and Steven and Fraser (1974) found four ectopic pregnancies in a retrospective analysis of 82 pregnancies occurring after failure of an IUCD. The pregnancy rate with the device in situ is around 2 per 100 women per year (Vessey, personal communication).…”
Section: Intrauterine Contraceptive Devicesmentioning
confidence: 76%
“…This is 2.5 to 5 times more often than in other women 22,24,25 . More than half of the spontaneous abortions in IUD users occur in the second trimester 20,26 . Because infection can occur in any pregnancy with an IUD in place, the IUD should be removed as soon as pregnancy is confirmed 13,27 .…”
Section: Discussionmentioning
confidence: 99%
“…Some 50-60% of uterine pregnancies spontaneously abort if the IUD is not removed [18][19][20][21][22][23] . This is 2.5 to 5 times more often than in other women 22,24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…All 5 anomalies were distinct (bald spot, eyelid ptosis, lipoid tumor, congenital hip dislocation, spina bifida). At least four other authors have also failed to detect an association between IUDs and anomalies [63][64][65][66].…”
Section: Intrauterine Devices (Iud): Claims Of Teratogenicitymentioning
confidence: 99%